Reformasi Sistem Peradilan Pidana Anak di Indonesia Antara Diversi, Restoratif, dan Perlindungan Hak Anak - Panu, Ariyanti; Moonti, Roy Marthen; Ahmad, Ibrahim (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2025)
The juvenile criminal justice system in Indonesia has been reformed through the enactment of Law No. 11/2012 on Juvenile Criminal Justice Sistem (UU SPPA), but its implementation is still ineffective. This study aims to examine the ineffectiveness of the implementation of diversion and the imbalance between restorative aspects and the protection of children's rights in a repressive justice system. This type of research is normative, with statutory, conceptual and comparative approaches. The results of the study showed that limited understanding of the apparatus, lack of institutional support, and the still strong paradigm of punishment were the main obstacles. In conclusion, the reform has not fully reflected the principles of restorative justice and child protection. The author recommends strengthening the capacity of officials, cross-sector collaboration, and revitalizing the role of the community in supporting the implementation of diversion and the protection of children's rights as a whole.